2007
DOI: 10.1002/jmv.21011
|View full text |Cite
|
Sign up to set email alerts
|

Association of TGF‐β1 codon 25 (G915C) polymorphism with hepatitis C virus infection

Abstract: Cytokines play a key role in the regulation of immune responses. In hepatitis C virus infection (HCV), the production of abnormal cytokine levels appears to contribute to the progression of the disease, viral persistence, and affects response to therapy. Cytokine genes are polymorphic at specific sites, and certain polymorphisms located within coding/regulatory regions have been shown to affect the overall expression and secretion of cytokines. The aim of the present study was to identify potential markers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 61 publications
8
48
2
2
Order By: Relevance
“…Furthermore, TGFB1 genetic polymorphisms have been associated with higher systemic TGF-b levels and worse outcome in hepatic viral infections (Dai et al 2008;Pereira et al 2008). Viral-specific proteins have also been shown to enhance TGF-b production and its cellular activity.…”
Section: Viralmentioning
confidence: 99%
“…Furthermore, TGFB1 genetic polymorphisms have been associated with higher systemic TGF-b levels and worse outcome in hepatic viral infections (Dai et al 2008;Pereira et al 2008). Viral-specific proteins have also been shown to enhance TGF-b production and its cellular activity.…”
Section: Viralmentioning
confidence: 99%
“…1. Finally, 8 eligible studies including a total of 1,542 participants (910 cases and 632 controls) were identified (14)(15)(16)(17)(18)(19)(20)(21). A summary of the characteristics of each study, including first author, year of publication, ethnicity of cases and controls, genotyping methods, number of cases and Table I.…”
Section: Resultsmentioning
confidence: 99%
“…However, two studies were outside the expected 95% CI of Begg's funnel plot in the C vs. G, GC vs. GG and CC+GC vs. GG models. After excluding these two studies contributing to heterogeneity (16,18), there was no obvious asymmetry of Begg's funnel plot in the C vs. G, GC vs. GG and CC+GC vs. GG models, with Egger's test P=0.110, 0.147 and 0.204, respectively.…”
Section: Sensitivity Analysis and Publication Bias For Tgfb1 915g/c Pmentioning
confidence: 88%
See 2 more Smart Citations